Chapter Antennas for Space Applications: A Review - Yazgan, Efe (InTechOpen, 2020)
It is well known that antennas are inevitable for wireless communication systems. After the launch of Sputnik-1 which was the first artificial satellite developed by USSR (Union of Soviet Socialist Republics), telecommunication technologies started to develop for space excessively. However, significance of the antennas as first or final RF-front end element has not been altered for the space communication systems. In this chapter, after introducing telecommunication and antenna technologies for space, which space environmental conditions are to be faced by these antennas are summarized. Then, frequency allocation that is a crucial design factor for antennas is explained and tabulated. And finally at the last part, different types of antennas used in different space missions are presented with their functional parameters and tasks.